3x-5y-9=0

Simple and best practice solution for 3x-5y-9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5y-9=0 equation:


Simplifying
3x + -5y + -9 = 0
Reorder the terms:
-9 + 3x + -5y = 0
Solving
-9 + 3x + -5y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '9' to each side of the equation.
-9 + 3x + 9 + -5y = 0 + 9
Reorder the terms:
-9 + 9 + 3x + -5y = 0 + 9
Combine like terms: -9 + 9 = 0
0 + 3x + -5y = 0 + 9
3x + -5y = 0 + 9
Combine like terms: 0 + 9 = 9
3x + -5y = 9
Add '5y' to each side of the equation.
3x + -5y + 5y = 9 + 5y
Combine like terms: -5y + 5y = 0
3x + 0 = 9 + 5y
3x = 9 + 5y
Divide each side by '3'.
x = 3 + 1.666666667y
Simplifying
x = 3 + 1.666666667y

You can always share this solution

See similar equations:

| 12t^2+32t+16= | | 9y^4+6y^2=0 | | 2sec^2x=9tanx+7 | | 38+(-17)+(-12)= | | 6(1--4w)=-18 | | 108+(-56)=-56+2(-56) | | 8X-Y=112 | | 6(1--4w)=18 | | 6(1--4)=-18 | | 3-4x-x^3=x+1 | | (D^3+2D^2)y=x | | 7(A-7)+10=2(A-7) | | 2x-3=44x+3 | | 48+(-32)=32+2(-32) | | 3x^4-8x^3+6x^2+2=0 | | 2(-4+7x)=11x+10 | | -4y+3=-5 | | 2r-24=-27+3r | | 3x+25=7 | | 2r-25=-26+r | | X+2xX+3xX=180 | | Z^4-z^2=2 | | 3y-29-9y+34= | | 22-3(c-1)=3c+25 | | 5v-25=4(7v-2) | | 3(2x+2)=5x+1 | | 3(2x+2)=5x | | -4(x-5)+8=x+3 | | 3x-4w=0 | | 8(x+3)=4(x+12) | | -7m-2=2+7m | | 2x+6(x+1)=4x+30 | | 7(-3)-(-2)= | | .06x=49.2 | | p=5s-128 | | 3x-3=123-11x | | 13=-15b+4b | | 4y=-3(y+1) | | t*-3.2=-4.7 | | 8-12x^2=0 | | -40-2n=3(-8+2n) | | r*3.4=9.5 | | 7y-2(y+3)=29 | | x+12.5=16.75. | | cos(5x)+cos(7x)=cos(x) | | x+12.5=26.75 | | x+12.5=18.1. | | 6w^2+33w+36=0 | | 5x+99=12x-90 | | -16x+8y+40=0 | | 4x^2+3x=7 | | 4b^2+6=-24 | | 2y+4-3y=-9+y+5 | | 4b^2+6=24 | | f(x)=-4x^3-3x^2+2x-2 | | 2x+4x=300 | | S=2(3.3)rh | | 2x-3y=38 | | 2x-3y=3b | | 55=3x+4x+6 | | 2t^2+6= | | 33+(-17)+(-11)= | | x^3-3x^2+4x-9=0 | | -6(6.61x-3.21)=4.75 | | 4z-26=19+9z |


Related pages


tanx cosxfraction of 0.875132 prime factorizationsolve 2sinx 1 0percent to decimals calculator4x 2y 6solution x100lcm of 180find the prime factorization of 125delta 4709prime factorization of 630what is the prime factorization of 540the prime factorization of 144prime factorization for 196cos7pi3x derivativegcf of 81 and 64lcm finderwhat is 1e9what is 0.5 percent as a decimal6x-2y 480000000008.1.3gcf of 72 and 90mcmxl roman numeralswhat is 4.48 as a fractiongcf and lcm of monomials calculatorsimplify square root of 64what is 4.75 as a fractionsqrt 192solver quadratic equationis4326derivative of 2e 2xlcm of 63cosx cos2x cos3xprime factors of 255bx18what is the greatest common factor of 1202x 5y 713 16thsfactor 3x 2 17x 10calculator quadratic equationcox and cos109-20convert 625 to a fractionsolve 4x4sin5xlcm 5 7graph 3x 4y 81300-500what is 0.875 as a fractiongcf of 54 and 72derivative of x sinyfraction subtraction solverx 2 12x 4 03u 2v200000 euros to dollars1963 roman numeralssimplify sinx cosx0.625 as fractionthe prime factorization of 150square root of 4410.625 as a percentderivative of 2 3x2x cosxsimplify 3n-2m 2prime factorization of 344factor 5x 2 3x-2prime factorization of 79derivative ln 3xderiv of tan